New insight into antiphospholipid syndrome: antibodies to β2glycoprotein I-domain 5 fail to induce thrombi in rats - Paolo Durigutto; Claudia Grossi; Maria Orietta Borghi; Paolo Macor; Francesca Pregnolato; Elena Raschi; Michael P. Myers; Philip G. de Groot; Pier Luigi Meroni; Francesco Tedesco (Haematologica, 2019)
Clinical studies have reported different diagnostic/predictive values of antibodies to domain 1 or 4/5 of β2glycoproteinI in terms of risk of thrombosis and pregnancy complications in patients with antiphospholipid syndrome. To obtain direct evidence for the pathogenic role of anti-domain 1 or anti-domain 4/5 antibodies, we analyzed the in vivo pro-coagulant effect of two groups of 5 sera IgG each reacting selectively with domain 1 or domain 5 in lipopolysaccharide (LPS)-treated rats. Antibody-induced thrombus formation in mesenteric vessels was followed by intravital microscopy, and vascular deposition of β2glycoproteinI, human IgG and C3 was analyzed by immunofluorescence. Five serum IgG with undetectable anti-β2glycoproteinI antibodies served as controls. All the anti-domain 1-positive IgG exhibited potent pro-coagulant activity while the anti-domain 5-positive and the negative control IgG failed to promote blood clot and vessel occlusion. A stronger granular deposit of IgG/C3 was found on the mesenteric endothelium of rats treated with anti-domain 1 antibodies, as opposed to a mild linear IgG staining and absence of C3 observed in rats receiving anti-domain 5 antibodies. Purified anti-domain 5 IgG, unlike anti-domain 1 IgG, did not recognize cardiolipin-bound β2glycoproteinI while being able to interact with fluid-phase β2glycoproteinI. These findings may explain the failure of anti-domain 5 antibodies to exhibit a thrombogenic effect in vivo, and the interaction of these antibodies with circulating β2glycoproteinI suggests their potential competitive role with the pro-coagulant activity of anti-domain 1 antibodies. These data aim at better defining “really at risk” patients for more appropriate treatments to avoid recurrences and disability.